ANALISIS PENYALURAN KREDIT PADA BANK UMUM BUMN TAHUN 2011-2020 - Kambalu, Elis Putri; Susilowati, Dwi (Program Studi Ekonomi Pembangunan, 2021)
Credit distribution activities have a very important role for the economy, namely to support development and to improve the welfare of the community, while for banks the main source of income comes from lending activities. The purpose of this thesis research is to determine the Effect of Third Party Funds, Net Interest Margin and Capital Adequacy Ratio on Credit Distribution at State-Owned Commercial Banks in 2011-2020. The data analysis technique used is Multiple Regression Analysis using panel data. The results obtained by the researchers are Simultaneously TPF, NIM, and CAR have an effect on Credit Distribution with significant results. while partially Third Party Funds (TPF) have a positive and significant effect on Credit Distribution. This is indicated by the regression coefficient value of 0.9872 and the probability value of 0.0000. Net Interest Margin (NIM) has a positive and insignificant effect on Credit Distribution. This is indicated by the regression coefficient value of 0.0043 and the probability value of 0.5706. And the Capital Adequacy Ratio (CAR) has a positive and insignificant effect on Credit Distribution. This is indicated by the regression coefficient value of 0.0055 and the probability value of 0.1214.